Alpha Calcitonin Gene-Related Peptide Increases Cerebral Vessel Diameter in Animal Models of Subarachnoid Hemorrhage: A Systematic Review and Meta-analysis - Flynn, Liam M. C.; Begg, Caroline J.; Macleod, Malcolm R.; Andrews, Peter J. D. (Frontiers in Neurology, 2017)
Delayed cerebral ischaemia is a life-threatening complication after subarachnoid haemorrhage. There is a strong association between cerebral vessel narrowing and delayed cerebral ischaemia. Alpha calcitonin gene-related peptide is a potent vasodilator which may be effective at reducing cerebral vessel narrowing after subarachnoid haemorrhage. Here we report a meta-analysis of data from 9 in vivo animal studies identified in a systematic review in which αCGRP was administered in SAH models. Our primary outcome was change in cerebral vessel diameter and the secondary outcome was change in neurobehavioural scores. There was a 40.8 ± 8.2% increase in cerebral vessel diameter in those animals treated with αCGRP compared with controls (p < 0.0005, 95% CI 23.7 to 57.9). Neurobehavioural scores were reported in 4 publications and showed a standardised mean difference of 1.31 in favour of αCGRP (CI -0.49 to 3.12). We conclude that αCGRP reduces cerebral vessel narrowing seen after SAH in animal studies but note that there is insufficient evidence to determine its effect on functional outcomes.